CONCEPTUALIZING KNOWLEDGE, COMPETITIVENESS AND EMERGING COLLABORATIVE TOURISM CLUSTER - Soonthonsmai, Vuttichat; Ingard, Apinya (CENTRAL ASIA AND THE CAUCASUS, 2022)
Enterprise cluster is based on the idea of ‘mutual dependence’ focusing on real participation of every supply-chain sector of which one strategy creating a strategic strength for the industries among severe competitiveness of the market. This research is aimed at examining the small and medium–sized tourism enterprises, knowledge and understanding of cluster development as determinants and analysing the competitiveness of the operators to determine managerial in developing tourism clusters. Mixed methodology was conducted in this study. 315 samples were purposively selected for quantitative method and 10 informants were selected for qualitative method. The findings showed that enterprises were clearly in the group of slightly high knowledge and understanding of tourism cluster development and in strongly competitiveness. The managerial development for sustainable tourism clusters can be potentially formulated in the form of the cooperation between tourism enterprises with supported by governmental units and educational institutes.